Komik sebagai Media Dakwah: Analisis Semiotika Kepemimpinan Islam dalam Komik âSi Bujangâ - Nasrullah, Rulli; Sari, Novita Intan (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2012)
Comics or cartoons are a kind of medium that can be used in dakwah. Through the comics, messages are represented by visuals which tend not to seem patronizing. One of the Islamic comic used as an example for this paper is the comic entitle